Testing methods of moisture content, critical moisture content, and germination of jamblang (Syzygium cumini (L.) Skeels) seed - Mi’raz Nur Indraeni; Faiza Chairani Suwarno; Abdul Qadir (Jurnal Penelitian Kehutanan Wallacea, 2019)
Jamblang (Syzygium cumini (L.) Skeels) researches are still focused to identify the plant benefits, but that leads to efforts to obtain good seed quality hasn’t been done. This study aims to determine the moisture content testing method, the critical moisture content, and germination testing method (sowing media and first and final count of seed germination). Improving procedure for moisture content testing and identified the best media for germination testing was arranged in a Completely Random Design. Determining jamblang seeds critical moisture content was arranged in a Randomized Complete Block Design. The experiments were repeated four times. Moisture content with slicing method obtained 49.57%. Jamblang seeds critical water content is 41.61% with 50% germination. The best method of germination was sand medium with fresh seeds (90%). The first count of jamblang seed germination occurs on 32 days after sowing and final count on 83 days after sowing.